Eco-friendly protection of pine wood using copper nanoparticles biosynthesized from Cleistocalyx operculatus leaf extracts - Tran Thi Bao , Tram; Le, Tu Thi Anh (Maderas. Ciencia y Tecnología, 2026)
This research investigates the eco-friendly biosynthesis of copper nanoparticles (CuNPs) from Cleistocalyx operculatus (water banyan) leaf extracts for the sustainable preservation of pine wood Pinus kesiya (khasi pine). The study specifically targets protection against common wood-decaying fungi, including Aspergillus flavus ATCC 9643, Fusarium oxysporum ATCC 48112, and Penicillium citrinum ATCC 9849, as well as termites. CuNPs were synthesized under optimized conditions: 80 °C for 30 minutes using a rotary evaporator, at pH 11, with 20 mM copper sulfate, and a 1.5:1 plant extract to precursor ratio. Comprehensive characterization using UV-Vis spectroscopy confirmed a prominent absorption peak at 595 nm. Scanning Electron Microscopy and Transmission Electron Microscopy further validated their spherical morphology, high crystallinity, and an average size of 2 ± 1 nm. Wood durability was evaluated through laboratory tests of fungal and termite resistance To assess the effects of different CuNPs treatments on fungal resistance and termite resistance, a one-way ANOVA was employed. Significant differences were found among the treatment groups (P<0,05). Duncan's multiple range test was performed using SPSS Statistics version 26, with statistical significance set at α = 0,05. The findings demonstrated a clear concentration-dependent efficacy of CuNPs. Treated wood samples exhibited significantly enhanced fungal and termite resistance, displaying notably reduced weight loss (approximately 10-15 %) compared to untreated controls (20-30 %). Furthermore, even at the lowest tested dosage, a substantial termite mortality rate of 43,17 % was observed, highlighting the potent bioactivity of the biosynthesized CuNPs. These results support the potential of Cleistocalyx operculatus-mediated CuNPs as an environmentally sustainable substitute for conventional, often harmful, wood preservatives. This green approach offers a sustainable alternative for wood protection and shows promise for broader applications of eco-friendly nanomaterials.